Vibrational spectra of hexaaquacomplexes. XII. On the possible anion disorder in selenate alums: prediction of the crystal structure and vibrational spectra of KAl(SeO4)2·12H2O and related alums - Vladimir M. Petruševski (Macedonian Journal of Chemistry and Chemical Engineering, 2015)
A survey is given for the crystallographic and vibrational spectroscopic results of a number of alums. From both types of results (structural and spectroscopic) it is positively known that the sulfate α-alums exhibit orientational disorder of the sulfate anions along the threefold symmetry axis. Both IR and Raman spectra confirm the finding for sulfate disorder in KAl(SO4)2·12H2O. Only the Raman spectra show clearly that the sulfate anions in many K, Tl and Rb are indeed disordered, in excellent agreement with the crystallographic results [1]. The disorder depends on the nature and size of MI cations in the structure, the smaller the radius, the larger the disorder. No anion disorder has thus far been detected in selenate alums. The structure prediction of KAl(SeO4)2·12H2O allows the existence of disorder of the selenate groups. The latter seems to be corroborated by the study of the Raman spectra of selenate α alums. It is thus worthwhile to have the crystal structure of KAl(SeO4)2·12H2O refined, in order to check this prediction and as an additional check of the general explanation for the sulfate anion disorder in alums, offered earlier [1].